Older adults make sense of their suicidal behavior: a Swedish interview study - Hed, Sara; Berg, Anne Ingeborg; Wiktorsson, Stefan; Strand, Jennifer; Canetto, Silvia Sara; Waern, Margda (Frontiers in Psychiatry, 2024)
The aim of this study was to explore how individuals aged 70 or older living in Sweden understood a recent suicidal act, and what changed in them and around them in the aftermath.Method: Four women and five men (age range 71-91 years) receiving care at a geriatric psychiatric outpatient clinic in a large Swedish city took part in two interviews about their most recent suicidal act. Most of the women and none of the men had engaged in prior suicidal acts. Interpretative phenomenological analysis was employed.The suicidal act was explained as a response to losses (in physical and cognitive functions, social roles and relationships) that rendered previous coping strategies unviable.The participants reported being dependent on a healthcare system that they experienced as indifferent and even dismissive of their suffering. The suicidal act was described as an unplanned act of despair. Positive changes followed for participants who reported having had suicidal ideation prior to the suicidal act and had insights into its triggers. Some gained access to needed medical care; others developed greater awareness of their psychological needs and became more effective at coping. Individuals who said that they had not had suicidal thoughts prior to the suicidal act and could not explain it reported no positive change in the aftermath.The respondents' narratives indicated gendered themes.Discussion: Participants' age-related losses were in many cases exacerbated by negative interactions with health care providers, indicating that continued attention needs to be given to implicit ageism in medical professionals. The suicidal acts were described as impulsive, which was unexpected because a dominant belief is that older adult suicidal behavior is planned. One reason for the discrepancy may be that this study focused on nonfatal acts, and planned acts may be more likely to be fatal. Another reason could be shame due to suicide stigma. Alternatively, these acts were truly unplanned. The older adult suicide planning question should be addressed in larger studies across geographical and cultural settings.Future studies should also include questions about gender norms of suicidality and separately examine women's and men's data.